Sliding mode controller for a stepper motor - Nor Shah, Mohd. Badril (2010)
Stepper motor is an electromechanical actuator widely used as positioning device due to its small size, reliable and relatively low maintenance cost. Furthermore, the permanent-magnet stepper motor gives better torque/weight ratio than the DC motor. However, the control problem of the stepper motor is complex due to the nonlinearities, the load torque perturbation, and the parameter uncertainties. Static Sliding Mode Controller (SMC) has been used in this project to give robust performance of stepper motor under various system conditions. The stepper motor is treated as differently flat system in which this approach has been formulated as a 'decouple' linear system leading to the simpler controller design. The dynamic equation of stepper motor is transformed into a class of nonlinear system representation by using a method known as Direct-Quadrature (DQ) transformation. A sliding surface is constituted by the direct current supply stabilization error and rotor angular position error. The implementation of designed static sliding mode controller is performed in simulation using MATLAB Simulink. The controller demonstrates that the response of a permanent magnet stepper motor is improved especially when driving at high inertia load and also robust to parameter uncertainties, disturbance and load torque perturbation.